2017
DOI: 10.23917/reaksi.v2i1.3682
|View full text |Cite
|
Sign up to set email alerts
|

Perspektif Positif Praktik Manajemen Laba: Kajian Empiris Pada Perusahaan Manufaktur Go Publik Di Bursa Efek Indonesia

Abstract: The earnings management practice has a positive and negative perspectives. This study aimed to analyze the effect of earnings management, corporate performance, quality audits, and Investment opportunity set to cost of equity companies are included in the Islamic index (JII) and conventional index (LQ-45). Measuring the earnings management used a short-term discretionary accruals (STDA) model. There were 461 companies (257 companies LQ-45 and 204 companies JII) taken by purposive sampling. Data was analyzed us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 4 publications
0
2
0
2
Order By: Relevance
“…The study results (Loyme and Yusuf, 2017) found that earnings management had no positive and significant effect on earnings management. (Wiyadi et al, 2017) states that the anticipation of earnings management causes the effect of earnings management on the cost of equity capital by investors in making decisions on their investments.…”
Section: Discussionmentioning
confidence: 99%
“…The study results (Loyme and Yusuf, 2017) found that earnings management had no positive and significant effect on earnings management. (Wiyadi et al, 2017) states that the anticipation of earnings management causes the effect of earnings management on the cost of equity capital by investors in making decisions on their investments.…”
Section: Discussionmentioning
confidence: 99%
“…While the remaining 70.1% influenced by other factors not examined in this study such as product image, consumer attitude. In 2017, Wiyadi et al conduct researched titled "Variables That Influence Power Ability Buy House", this research examines variables of purchasing power that affect the ability to buy a house in Malang City, Eat Java, Indonesia [19]. The result of the research shows that loan variable PUMP-KB PT.…”
Section: Theoretical Frameworkmentioning
confidence: 98%
“…Hal ini mengacu pada keberhasilan suatu perusahaan dalam mengendalikan sumber daya dan pendapatan dari usahanya. Menurut penelitian Wiyadi et al, (2017) kinerja perusahaan yang baik berdampak pada modal yang lebih kecil. Hal ini karena investor tidak merasakan penurunan keuangan di perusahaan yang mereka yakini berjalan dengan baik.…”
Section: Pendahuluanunclassified